A preliminary study on the relationship between cultural identification, racial discrimination, and well-being of Chinese Malaysians Young adults - Ting, Rachel Sing Kiat; Lim, Xin Jean; Lim, Joy Yung Re; Choo, Jia Yee (Springer, 2023)
It was well documented that racial minorities struggle with discrimination that jeopardizes their mental well-being. However, the interaction between cultural identification (CI) and mother tongue (MT) on perceived discrimination among minority communities was unclear. This study adopted a cross-sectional survey to investigate how different Chinese in Malaysia (CIM) groups experience in-group versus out-group discrimination based on their MT, and its impact on well-being. We hypothesized that (1) different CIM-MT groups would differ in their in-group discriminations; (2) there would be a pathway from CI to discrimination and to mental well-being; (3) MT would have a moderation effect on the pathway. A standardized online survey measuring CI (national vs. ethnic), perceived discrimination (in-group vs. out-group), and mental well-being (life satisfaction vs. mental distress) was administered to CIM college students. Analysis using ANCOVA and PLS-SEM (N = 288) showed that the English-MT group reported higher in-group discrimination than the Chinese-MT group. Moreover, the PLS-SEM analysis showed that ethnic identity, not national identity, displayed a significant negative association with in-group discrimination, which then significantly predicted mental distress in general. Furthermore, MT was a significant moderator between national identity and out-group discrimination. The findings confirmed that MT could predispose CIM to different exposure of racial dynamics and contexts. In lieu of the detrimental effect of both forms of racial discrimination, we advocate for culturally responsive mental health services for ethnic minorities around the world.